Exploring In-Service Science Teachers' Self-Perceptions of Competence and Pedagogical Approaches to Socioscientific Issues in Education - Arberore Bicaj; Fatlume Berisha; Rachel Gisewhite (MDPI AG, 2024)
Global education experts are increasingly prioritizing scientific literacy development. Science education is key to enhancing scientific literacy, fostering social responsibility, and supporting economic growth by equipping individuals with essential scientific knowledge and skills. In the past two decades, socioscientific issues (SSI) have greatly influenced science education research, improving students' ability to apply scientific knowledge in real-world contexts and advancing functional scientific literacy. Given the strong evidence that socioscientific issues (SSI) enhance scientific literacy and social responsibility skills, understanding SSI role in science education is crucial for developing countries aiming to boost economic and social growth. This research aimed to understand the in-service science teacher's self-perception, knowledge, and experiences, as well as the benefits and challenges of integrating socioscientific issues into education. This qualitative research analysis employed a thematic analysis approach to research and data analysis from the responses of 54 in-service science teachers. All participants responded to the online open-ended questionnaire, which consisted of open-ended questions. The results highlight that in-service science teachers face challenges such as inadequate school environments, social pressures, and limited professional support, all of which hinder effective teaching of socioscientific issues. Furthermore, most of the in-service science teacher participants in the study were unaware of SSI, which suggests that there is a need for targeted professional development. The research suggests that it is crucial to address these challenges and enhance the knowledge and understanding of in-service science teachers regarding SSI to facilitate curriculum reform and the overarching goal of promoting citizens' educational and economic development.